The Analysis of Associative Fields of Words-Stimuli МИР / МИР / МІР (PEACE) in East-Slavonic Languages - Terekhova, Diana (East European Journal of Psycholinguistics, 2014)
The    free  associative  experiment    is  the  traditional  language  awareness   method of studying.   Language  consciousness   investigations   via   associative   experiments permit   to   represent   the system of linguistic consciousness (not only the extent of a certain words in their reflections in mind) as a coherent and cohesive unit. It shows a unique picture  of   the  world in each culture. The article is devoted to comparative psycholinguistic analyses of the associative fields of the words-stimuli МИР / МИР / МІР (peace). Common and specific features of the corresponding parts of the world reflection in minds of the Ukrainians, the Russians and the Byelorussians are described in it. Associative gestalt was used in our research to make a   structure  of  all the research associative materials. The nuclear and periphery of the associative gestalt was defined in each language under analyses. The largest differences are found: 1) in different number of zones among three gestalts; 2) in existence of separate zones just in a certain gestalt in contrast to others; 3) in different zones’ degree that defines their rank and position in gestalts; 4) in quantitative and qualitative zones’ composition; 5) in gestalt kernels.  ReferencesTarasov, Ye. F. (2000). Aktualnye problemy analiza yazykovogo soznaniya [The key issues ofthe linguistic consciousness analysis]. Yazykovoye soznaniye i obraz mira. 24–33.Solovyova, N. V. (2005). Leksika voyni i mira v russkoy delovoy pismennosti kontsa XVI–XVII vv.: lingvokognitivniy aspect [The Lexis of War and Peace in Russian Business Documents ofthe Late XVI-XVII Centuries: Linguo-cognitive Aspect]. Minsk: Byelorussian State University.Stepanov, Yu. S. (2001). Konstanty: Slovar russkoy kultury [The Constants: Dictionary ofRussian Culture]. Moscow: Akademicheskiy Proekt.Zhayvoronok V. V. (2006) Znaky ukrayinskoi etnokultury. [Signs of the UkrainianEthnoculture]. Kyiv: Dovira.Sternin, I. A., Bykova, G. V.(1998) Koncepty i lakoony [Concepts and Lacunes]. Yazykovoyesoznaniye: formirovaniye i funkcionirovaniye, 33-39.